Homegardens in north-eastern Portugal: former features, roles, gendered knowledge and practices - Carvalho, Ana Maria (Gaia Scientia, 2016)
This study describes general homegardens former features and primary functions in a protected rural area of the North-eastern Portugal, the Natural Park of Montesinho, and focuses on fundamental socio-cultural roles intertwined with economic and ecological purposes registered during a three year period, from 2002 to 2005, using ethnographic methodologies. The gendered nature of local homegardens is also discussed: former homegardens used to be female domains managed according to female values and ideals. Thus, gendered knowledge and women’s intentions and practices are reported throughout the text. Homegarden practices have maintained for a long time traditional knowledge, local culture and techniques and plant varieties. The complex structure and intertwined roles of Montesinho homegardens have been neglected by research and rural development professionals, perhaps because women, who were the primary experts and knowledge holders, were often marginalised Changes in rural societies and the modernisation of lifestyles have affected homegardens’ relevance, roles and management and have influenced gardeners’ behaviour, the persistence and transmission of traditional knowledge and homegardens prevalence as important garden sites. However, some participants considered that with new economic opportunities such as agritourism and organic produce, and the limited alternatives in rural areas, that situation could reverse in the medium term. . In this instance, transmission of homegardening knowledge and practice would be vital